White Blood Cell Differentiation Based on Toll-Like Receptor 4 (TLR4) Gene Polymorphism in Local Indonesian Chickens - Maskur, Maskur; Jan, Rahma; Rozi, Tapaul; Kasip, L.; Muhsinin, Muhammad (Jurnal Biologi Tropis, 2024)
Toll-like Receptors (TLRs) genes are a group of genes that transcribe TLRs proteins which act as receptors on the surface of phagocytic cells to recognize molecular patterns of pathogenic microbial components. This research aims to identify the variability of the TLR4 gene and its relationship with blood profiles in local Indonesian chickens. The samples used to identify TLR4 gene diversity in local Indonesian chickens were 135 samples. Research methods include DNA extraction, PCR amplification, RFLP analysis, and genotype determination. The genotyping results in the research were associated with a complete blood profile so that a genotype was obtained that could be used as a marker for resistance traits based on the blood profile. The results of this study showed that the TLR4 gene was polymorphic with three genotype types and an allele frequency of more than 0.01 in each KUB, Sensi, and Broiler CP 707 chicken. The frequency of the GG genotype is the highest compared to the AG and AA genotypes. White blood cell concentration values showed variations in the three genotypes of TLR4 gene and were still within normal standards, although statistically the differences were not significant.